Representasi Gender Dalam Film La La La Land (2016) - Ramadhan, Maulana Fajar (CV. ITTC INDONESIA, 2026)
Film as a mass medium plays a significant role in constructing and representing social realities, including gender representation. La La Land (2016) is an interesting subject of study as it portrays the dynamics of male and female roles within the highly competitive entertainment industry. This study aims to analyze how gender representation is constructed through characters, narratives, and visual elements in La La Land. The research employs a qualitative approach using Roland Barthes’ semiotic analysis and Stuart Hall’s representation theory, supported by Laura Mulvey’s feminist media theory and Judith Butler’s gender performativity theory. The findings reveal that the film still contains elements of the male gaze, particularly in its depiction of the female character during casting scenes, while simultaneously presenting an empowered and independent female representation. Furthermore, the film portrays modern masculinity as emotional and non-dominant. The study concludes that La La Land reflects a shift in gender representation in contemporary popular cinema, although certain gender biases remain present.